Faktor-faktor yang berhubungan dengan kecemasan dan depresi pada pasien diabetes melitus tipe 2 - Pipin Nurhayati (Health Sciences and Pharmacy Journal, 2020)
Physical, psychological, and social changes are the changes that occur due to the various complications that accompany the disease DM type 2. Psychological changes that occur, such as stress, and depression. The purpose of this study is to determine the factors related to anxiety and depression in patients with type 2 diabetes mellitus. This type of research was descriptive with cross sectional design. Sampling technique used total sampling with 60 people. The instrument used DASS 42 and BDI questioner. Data were analyzed by chi square. Chi square test results obtained factors related to anxiety in patients with type 2 diabetes mellitus are age (p value = 0,000), long suffering from type 2 DM (p value = 0,000), education (p value = 0,040), comorbidities (p value = 0,000) and family support (p value = 0,000). While factors which were not related to anxiety in patients with type 2 diabetes mellitus were impaired functional ability (p value = 0,517). Factors that related to depression in patients with type 2 DM were age (p value=0.007), education (p value = 0,001), comorbidities (p value = 0,000) and family support (p value = 0,040). While factors unrelated to anxiety of patients with type 2 DM are long period of type 2 DM (p value = 0,797) and functional ability disorder (p value = 0,435). Conclusion of the factors related to anxiety of patient with type 2 DM are age, long period of type 2 DM, education, comorbidities and family support, while factors that unrelated to anxiety of patients with type 2 DM are functional ability disorder, factors that related to depression of patients with type 2 DM are age, education, comorbidities, and family support, while factors that unrelated to depression of patients with type 2 DM are long period of type 2 DM and functional ability disorder.